Psychiatry - Thornhill, Joshua T. , IV (National Medical Series For Independent Study, 2012)
"In this sixth edition of NMS Psychiatry, each chapter as well as the drug appendix has been updated to include the latest medications and treatment protocols. New chapters have been added on the emerging fields of emergency and geriatric psychiatry. In addition, we have continued to revise, update, and add new questions to each chapter and to the comprehensive examination to help students prepare for National Board of Medical Examiners (NBME) Subject examinations as well as the United States Medical Licensing Exam (USMLE) Step 2"--Provided by publisher.